Nontraumatic Acute Elevation of Pancreatic Enzymes following Percutaneous Nephrolithotomy: A Rare Complication - Nikolaos Ferakis; Antonios Katsimantas; Georgios Zervopoulos; Vasileios Klapsis; Spyridon Paparidis; Filippos Venetsanos; Konstantinos Bouropoulos (Case Reports in Urology)
Herein, we report the case of a 48-year-old female who developed nontraumatic acute pancreatitis following left supracostal Percutaneous Nephrolithotomy. Three hours postoperatively, the patient developed fever with signs and symptoms consistent with hydrothorax, which was confirmed radiologically and was managed conservatively. The following days, the patient developed manifestations of Systemic Inflammatory Response Syndrome with epigastric pain, nausea, and vomiting. Blood, urine, and sputum cultures were negative. Serum amylase and lipase levels were elevated 3 and 13 times above the normal level, respectively. Imaging studies revealed no pathologic findings from pancreas. These findings were consistent with the diagnosis of acute pancreatitis.